(untitled) (Inflexion Point Magazine, 2024)
Energy is vital for human activities and traditionally, fossil fuel sources like coal, petroleum, and natural gas are the primary source to satisfy energy demands due to their easy extraction. Because fossil sources are non-renewable and generate environmental degradation, toxic gases, and soil and water contamination, it has been a priority to find alternatives to supply energy demands without causing environmental damage by seeking renewable natural resources that allow their use and reduce the negative environmental impact. This paper aims to present the diverse types of alternative energy obtained from renewable natural resources such as sun, wind, tides, and water, among others, that generate development despite having a low level of contamination.